Axial strength of short concrete-filled plastic tubes. (October 2020) - Abdulla, Nwzad Abduljabar
Abstract: The axial compressive behavior of concrete-filled plastic tube (CFPT) with five different cement–admixture combinations were examined. A commercially available modified polycarboxylate superplasticizer used at five different concentrations. The plastic tube was an un-plasticized polyvinyl chloride (uPVC) made up of three layers: a blue layer sandwiched between two white layers to achieve solid wall construction. Test results showed that the strength of the CFPT specimens influenced by the increase in superplasticizer dosage up to an optimum dosage. Further increase in the admixture-cement ratio had an adverse effect on strength enhancement. To assess the performances of CFPT specimens under monotonic axial compression, an extensive database comprising the test results of the 157 CFPT column established. The database supplemented by the sum of eighteen test results from the current experimental study used to assess the applicability of ten existing FRP-confined concrete, two steel-confined concrete, and one CFPT strength model to predict the strength of CFPT specimens. By considering the light confinement mechanisms of the tube and general regression analysis, four simple ultimate strength models were proposed based on the database assembled in the present study. Three different statistical indices, the coefficient of determination (R 2 ), the Root Mean Square Error (RMSE), and Average Absolute Error (AAE), were used to assess the performance of the strength models. The proposed four strength models yielded the best fitting results compared with the predictions from the existing ten FRP-confined concrete, two steel-confined concrete, and one CFPT strength model.